Challenges in the Implementation of the 2024 Simultaneous National and Regional Elections in the Four New Provinces of Papua: Tantangan Penyelenggaraan Pemilu dan Pilkada Serentak Nasional 2024 di Empat Provinsi Baru Papua - Jauhar Nashrullah (Universitas Islam Indonesia, 2023)
The 2024 election event experienced new dynamics when in 2022 the government and the DPR agreed to form four new provinces in Papua. It is certain that these four new provinces will be included in the simultaneous elections and local elections in 2024. However, the presence of new provinces in the midst of the election stages raises various problems. This research is a type of normative juridical research, using statutory and conceptual approaches. Primary and secondary legal materials collected through literature studies will be analyzed using descriptive-analytic techniques. The results of this study describe that the presence of four new provinces in Papua has added to the dynamics and challenges of holding the 2024 National General Election and Regional Head Elections, which were previously filled with complexity. The formation of the new province of Papua, which was late and carried out when the election stages had already begun, forced the government to issue a Perppu. Some of the challenges in organizing the 2024 political contest in the new province of Papua are as follows: 1) The potential for using the noken system in the Highlands and Central Papua Provinces, 2) Provision of infrastructure and facilities to support general elections and 3) Potential defense and security disturbancesKeywords: 2024 National Simultaneous, 2024 Simultaneous Election, Regional Elections New Papua Provinces AbstrakPerhelatan pemilihan umum 2024 mengalami dinamika baru ketika di tahun 2022 pemerintah dan DPR sepakat membentuk empat provinsi baru di Papua. Empat provinsi baru ini dipastikan akan diikutsertakan dalam pelaksanaan Pemilu dan Pilkada serentak di tahun 2024. Namun hadirnya provinsi baru ditengah tahapan Pemilu menambah problematika. Penelitian ini merupakan jenis penelitian yuridis normatif, menggunakan pendekatan perundang-undangan dan konseptual. Bahan hukum primer dan sekunder yang dihimpun melalui studi kepustakaan akan dianalisis menggunakan teknik analisis-deskriptif. Hasil kajian ini menguraikan bahwa hadirnya empat provinsi baru di Papua semakin menambah dinamika dan tantangan penyelenggaraan Pemilu dan Pilkada Serentak Nasional 2024, yang mana sebelumnya telah dipenuhi kompleksitas. Pembentukan provinsi baru Papua yang sempat terlambat dan dilakukan ketika tahapan Pemilu sudah dimulai membuat pemerintah harus mengeluarkan Perppu. Adapun beberapa tantangan penyelenggaraan kontestasi politik 2024 di provinsi baru Papua sebagai berikut: 1) Potensi penggunaan sistem noken di Provinsi Papua Pegunungan dan Papua Tengah, 2) Penyediaan infrastruktur dan sarana penunjang pemilihan umum dan 3) Potensi gangguan pertahanan dan keamanan.Kata Kunci: Pemilu Serentak 2024, Pilkada Serentak Nasional 2024, Provinsi Baru Papua